Teachers' Creativity in EFL Teaching Classroom of Vocational High Schools at Barru Regency - Rahmania Ningsih; Haris Sunubi; Zulfah; Arqam; Ambo Dalle (Universitas Muhammadiyah Palu, 2025)
Creativity is crucial for teachers, particularly in teaching English as a foreign language (EFL) in vocational schools. In vocational schools, teacher creativity is essential to creating engaging and relevant learning environments, motivating students, and preparing them for professional challenges. This research aims to describe teacher creativity in teaching English at vocational schools in Barru. A descriptive qualitative research design was used, employing interviews and documentation as research instruments. The subjects were five teachers from three vocational schools at Barru Regency. Data processing included data reduction, data display, verification, and conclusion drawing. The results showed that EFL teachers in Barru's vocational schools demonstrate varied creativity by adapting lesson plans to meet curriculum standards and incorporating innovative methods like collaborative learning and community projects. A student-centered approach leverages diverse media and technology to enhance engagement and cater to different learning styles. Effective classroom management and a deep understanding of students' needs further support creative strategies. Methods are continuously reflected upon and adjusted based on student feedback, addressing challenges through collaboration and ongoing professional development. The creative use of technology and the development of unique teaching materials, such as Reading Journals, Weekly News Journals, Digital Storytelling, and collaborative projects, highlight a dedication to providing engaging and relevant learning experiences